PRINCIPLES OF DIAGNOSIS AND TREATMENT OF ACUTE PURULENT-DESTRUCTIVE LUNG DISEASES - Alisher O.Okhunov; Kakhramon X.Boboev; Azizbek F.Valijonov; Shirina A. Valijonova (Scholar Express Journals, 2022)
Thanks to the organization and improvement of diagnostic methods, new methods of treatment, surgical techniques, significant progress has been made in the treatment of acute purulent-destructive lung diseases (APDLD). However, this problem remains relevant today. In recent years, there has been an increase in the number of patients with severe and complicated forms of AHDD [1] As we know, according to studies [2,3,4] the percentage of development of pulmonary-pleural complications in lung abscesses ranges from 30% to 70%, and the incidence of gangrenous forms from 28% to 74%. Despite various approaches to the treatment of AHDD, the results of complex treatment can hardly be considered satisfactory. There is still a high mortality rate, which ranges from 12.7% to 77.8% in various forms of purulent-necrotic process. Management and treatment of patients with this pathology requires an individual approach and a set of therapeutic measures.
Keywords: Acute Purulent-Destructive Lung Diseases(APDLD); Acute Lung Abscess; Lung Gangrene; Treatment